Use of Library Resources and User’s Satisfaction - Saikia, Mukesh; Gohain, Anjan (Journal of Information and Knowledge, 2015)
This study is an investigation of, use of library resources, users’ satisfaction of library resources and services and information seeking behavior of students and research scholars of Tezpur University. 200 questionnaires were distributed among students and research scholars of Tezpur University to collect relevant data. 79.5% (159) library users responded. Library is playing a vital role to meet multidimensional demands of students, and research scholars. It is felt that user guidance is necessary to help library users to meet their information needs and to make users aware of the available library resources and services.